2020
DOI: 10.1016/j.jvb.2020.103401
|View full text |Cite
|
Sign up to set email alerts
|

Political skill camouflages Machiavellianism: Career role performance and organizational misbehavior at short and long tenure

Abstract: Highlights for review  We jointly tested socioanalytic and mimicry deception theory  We predicted career role performance and counterproductive work behavior  We used a two-study triangular research design with 1,438 study participants  Political skill masked Machiavellianism as predicted by socioanalytic theory  Mimicry deception theory was only partially supported by the data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 80 publications
(135 reference statements)
3
15
0
Order By: Relevance
“…Support for H2 also aligns with previous research that identified the important moderating role of political skill in predicting unethical outcomes (Baloch et al, 2017;Zhao et al, 2013). In line with research showing that political skill can camouflage Machiavellianism (Blickle et al, 2020), it seems that high maverickism has the potential to alter the expression of political skill from being neutral with respect to unethical decision-making to one facilitative of adverse results. This research makes an important contribution by providing a useful starting point for future research aimed at better understanding the potential boundary conditions of maverickism and political skill.…”
Section: Discussionsupporting
confidence: 85%
“…Support for H2 also aligns with previous research that identified the important moderating role of political skill in predicting unethical outcomes (Baloch et al, 2017;Zhao et al, 2013). In line with research showing that political skill can camouflage Machiavellianism (Blickle et al, 2020), it seems that high maverickism has the potential to alter the expression of political skill from being neutral with respect to unethical decision-making to one facilitative of adverse results. This research makes an important contribution by providing a useful starting point for future research aimed at better understanding the potential boundary conditions of maverickism and political skill.…”
Section: Discussionsupporting
confidence: 85%
“…This is not only another verification of role theory in the Chinese context but also an enrichment of the antecedent variables of WFC. Moreover, previous studies have examined the positive effect of employees' PS on their promotion probability [21], career development [50] and performance rating [93]. This study extends the outcome of employee PS by proving the negative effect of PS on WFC.…”
Section: Theoretical Implicationssupporting
confidence: 55%
“…In supervisor-subordinate interaction, the leader's needs are often not publicized. Employees high on social astuteness can quickly and accurately understand the leader's intentions through keen observation [50]. Moreover, employees with strong abilities in interpersonal influence have good communication skills [51].…”
Section: Employee Political Skill and Supervisor-subordinate Guanximentioning
confidence: 99%
“…Our results contribute to the investigation of Machiavellianism's manifestation in work and leadership contexts. Jones (2014) speculated that Machiavellians with very high social skill penetrate organizations in a long-term process, for which Blickle et al (2020) found partial support. Thus, strong political skill may provide Machiavellian leaders with the impulse control in social situations needed to pursue a long-term goal, while maintaining ulterior motives.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, prior studies demonstrate that political skill relates to transformational leadership, which mediates leadership effectiveness (i.e., Blickle et al, 2014; Ewen et al, 2013; Wihler et al, 2016). Furthermore, leadership situations behaviorally activate political skill in dark personalities (Kholin et al, 2020), and highly politically skilled Machiavellians' career behaviors follow long-term career goals (Blickle et al, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%